3D-maaperämallinnus hydrogeologisessa tutkimuksessa : esimerkkinä Kulopalokankaan pohjavesialue Äänekoskella - Koivulehto, Liisa (Helsingfors universitet, 2016)
Äänekosken Energia Oy is planning an artificial groundwater recharge plant in Äänekoski Central Finland. Consulting company Ramboll is in charge of the water intake project that is situated at an important groundwater recharge area, Kulopalokangas. The aim of this study is to collect data from previous studies in the area, create a three-dimensional geological model of the study area's bedrock surface and sediments as well as discuss their effect on groundwater flow. Further objective is to test modelling software Leapfrog Geo and its suitability in this type of study. The study area is characterized by an esker formation that was deposited during the deglaciation of the Weichselian glaciation. This esker originates from a end moraine formation in Central Finland that formed at the rim of the continental ice sheet about 11 000 years ago. The bedrock is relatively homogenous and there are no faults. The bedrock is considerably exposed in the area and the sediment package consists of coarse sand and gravel units in the central part of the study area, whereas finer material is located at the rims and on the outside of the esker. Geological and geophysical investigations have been conducted previously within the water intake project. The data used in this study was gathered from seismic refraction surveys, drilling data and groundwater table measurements. The input data was in point data and drill hole format, and the surfaces and volumes of soil units were created subsequently. Cross sections were created to illustrate inner structures of the sediments throughout the area. The results are presented as a digital elevation map of bedrock, a groundwater map, images and cross sections of the model. They show the distribution of soil units. In addition, they provide information of the areas for artificial recharge as well as factors effecting the groundwater flow. The bedrock surface forms a NW-SE oriented depression valley that is filled with soil units. A two-meter thick unit of till is located above the bedrock and ...